Evaluation of Child-Friendly School Policies at SMPN 14 Surabaya - Waming Gading Ardy Pratama; Mufarrihul Hazin; Kaniati Amalia; Hari Setyawan (Prodi PAI STIT Sunan Giri Bima, 2026)
This study aims to evaluate the implementation of the Child-Friendly School (SRA) policy in SMP Negeri 14 Surabaya using James E. Anderson's policy evaluation theory which includes aspects of policy substance, policy implementation, and policy impact. The research uses a qualitative method with data collection techniques through interviews, observations, documentation, and questionnaires to school principals, teachers, and students. The results of the study show that the SRA policy was implemented in response to the increase in bullying behavior in the school environment. From the substance aspect, the policy is considered relevant to the needs of schools and has a clear legal basis. In the implementation aspect, schools involve all school residents through the division of tasks, teacher training, the application of positive discipline, and the provision of child-friendly support facilities. The impact of the policy shows positive changes in the form of increased learning comfort, better relationships between teachers and students, and the creation of a safer and conducive school environment. However, bullying and violent behavior is still found in the student environment, so it is necessary to evaluate and strengthen policies in an ongoing manner.